Environmental factors and fish reproduction - Ribeiro, Cristiéle da Silva; Moreira, Renata Guimarães (Revista da Biologia, 2018)
Reproductive physiology of fish is a vast scientific field, which addresses a set of physiological processes essential for reproduction, from egg fertilization to sexual behavior and spawning. These processes are directly modulated by environmental factors which may directly or indirectly determine the reproductive success of a species.